2016
DOI: 10.1007/s00455-016-9728-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Dysphagia Presentation and Intervention Following Traumatic Spinal Injury: An Understudied Population

Abstract: Dysphagia is reported to be a common secondary complication for individuals with traumatic spinal injuries. Different etiologies of traumatic spinal injuries may lead to different profiles of swallowing impairment. We conducted a systematic review to determine the characteristics of dysphagia after traumatic spinal injury and to describe interventions currently used to improve swallowing function in this population. A comprehensive multi-engine literature search identified 137 articles of which 5 were judged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…By reviewing the description of the dysphagia, it appears that the pharyngeal phase is mostly impacted by a high-level SCI as the most reported symptoms were: residue in pyriform sinus or valleculae, poor laryngeal elevation, poor epiglottic closure, poor base of tongue movement, decreased pharyngeal peristalsis, decreased sensation and impaired upper oesophageal sphincter functioning (Ihalainen 2017; Lee et al 2016 ; McRae et al 2019 ; Papadopoulou et al 2013 ; Shem et al 2012 ; Valenzo et al 2016 ). According to Wolf and Meiners ( 2003 ), patients with a cervical SCI have difficulty protecting their airway because of respiratory difficulties, which is important to identify and manage early.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By reviewing the description of the dysphagia, it appears that the pharyngeal phase is mostly impacted by a high-level SCI as the most reported symptoms were: residue in pyriform sinus or valleculae, poor laryngeal elevation, poor epiglottic closure, poor base of tongue movement, decreased pharyngeal peristalsis, decreased sensation and impaired upper oesophageal sphincter functioning (Ihalainen 2017; Lee et al 2016 ; McRae et al 2019 ; Papadopoulou et al 2013 ; Shem et al 2012 ; Valenzo et al 2016 ). According to Wolf and Meiners ( 2003 ), patients with a cervical SCI have difficulty protecting their airway because of respiratory difficulties, which is important to identify and manage early.…”
Section: Resultsmentioning
confidence: 99%
“…There is little epidemiological data relating to SCIs in South Africa (SA), despite trauma-related injuries being considered as one of the quadruple burdens of disease (Pillay-Van Wyk et al 2016 ), but it is reported that around 75 million people have experienced some forms of SCIs (Joseph et al 2017 ). Literature trends stemming from a variety of economically developed countries, such as the United States of America and others in Europe, indicate that dysphagia is prevalent in the SCI population, but prevalence rates vary from 26% to 80% (Papadopoulou et al 2013 ; Valenzano, Waito & Steele 2016 ). One of the primary difficulties that occurs as a result of a higher (above C5) SCI is that of respiratory complications (Hagen 2015 ) including: insufficiency of respiratory muscle functioning, resulting in long-term ventilation and possible tracheostomy tube insertion; reduced vital capacity; and ineffective cough, pneumothorax and pleural effusion (Hagen 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the key feature of dysphagia in CSCI patients is not delayed swallowing but ineffective pharyngeal squeeze [26] making thickened fluids unsuitable as they are more challenging to clear from the pharynx and can increase damage to lung mucosa due to aspiration [37]. Similarly, a reliance on the cough reflex to signify aspiration is problematic especially for patients with inflated tracheostomy cuffs [38] or absent cough ability due to impairment to the vagus nerve [39]. Instead, instrumental assessments, such as FEES or VFS are recommended to identify laryngeal impairments that are asymptomatic at bedside [3, 23, 24, 26, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Ickenstein et al report an incidence of OD >50% within 72 hours of a new stroke. A systematic review by Valenzano et al found small case studies and definitions of dysphagia to be inconsistent for individuals who have experienced traumatic spinal injury, indicating the need for further research with a specific definition of dysphagia, as the broad definition of dysphagia implies impact along various sections or phases of the swallow. Further exploration can lend insight relevant to prevalence or incidences, given various medical conditions or factors.…”
Section: Statisticsmentioning
confidence: 99%